Nationalism, Unity, and Strategic Resilience: Nepal’s Evolving Security Paradigm - Acharya, Shreejana (Unity Journal, 2026)
Nepal’s unique geopolitical location, deep social diversity, and enduring history of safeguarding sovereignty situate nationalism and national unity at the core of its security discourse. From the foundational unification campaigns of Prithvi Narayan Shah’s Dibya Upadesh to Nepal’s contemporary leadership in global peacekeeping, national resilience has consistently emerged from the cohesion between the state and its diverse populace. In this light, this paper argues that an inclusive civic nationalism, grounded in respect for cultural plurality and a shared constitutional identity, functions as a strategic capital for national security. Such a strong unity enhances collective capacities, invigorates the country to promptly respond to crises, and strengthens international credibility and legitimacy. Employing a qualitative approach that analyses historical records, official policy documents, and secondary scholarly literature, this study examines how unity enhances resilience against modern multidimensional security threats. These risks include non‑traditional challenges like natural disasters (the 2015 earthquake), public health crises (the COVID‑19 pandemic), digital misinformation, and recent social unrest (the Gen‑Z Movement 2025). The research examines the evolution of Nepal’s security paradigm by analyzing the Nepali Army’s constitutionally defined role under civilian authority to assess how institutional restraint and adherence to constitutional democratic Values contribute to nationalism, national unity, and strategic resilience. The findings conclusively suggest that inclusively cultured nationalism strengthens Nepal’s adaptive capacity and provides the necessary social cohesion to address both internal polarization and complex cross‑border challenges. Ultimately, the study reasserts that the nation’s most enduring guarantee of stability rests upon the confidence and inclusion of its people.